(untitled) (Research, Society and Development, 2024)
Objective: To carry out a survey of the therapeutic response and the main resistance mutations related to the use of antiretroviral therapy in children born to HIV-positive mothers in a reference center in the city of Imperatriz, MA. Method: This is a retrospective, descriptive, cross-sectional study, carried out at the Regional Maternal and Child Hospital with a quantitative approach from 2006 to 2021. Using patient records, it was possible to access the Ministry of Health database through from the website https://laudo.aids.gov.br to collect therapeutic history, viral load and genotyping data. Results: The 34 children selected had an average age of 8 years, with an average time using antiretroviral treatment of 5.83 years. 100% of children used nucleoside analogue reverse transcriptase inhibitors, 88.2% non-nucleoside analogue reverse transcriptase inhibitors, 38.2% protease inhibitors, 47% integrase inhibitors. 47.1% were classified as therapeutic success, 26.4% as therapeutic failure and 20.6% as incomplete response. 80% of mutations were identified in (ITRN), 73.3% for (ITRNN), 46.7% for (IP) and 6.7% for (INI). Conclusion: The therapeutic success of the children in this study was lower than that reported in the literature. The number of children experiencing therapeutic success and the mutations identified highlight the need for better strategies to improve patient adherence and optimize the use of antiretroviral regimens.